2022
DOI: 10.3389/fpsyg.2021.823884
|View full text |Cite
|
Sign up to set email alerts
|

Social Communication of Transportation: A Bridge Model Connecting Tourism Destination and Psychological Perception

Abstract: As it is essential to explore the influence of social communications on transportation routes in tourism, this article aims to examine the impacts of social communications on transportation routes in the field of tourism and to further explore the relationship between tourism destinations and their psychological perceptions. In terms of links between different tourism destinations in space and time dimensions, our empirical analysis draws the following conclusions: (1) the behavior of tourist flow is a mediati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Tourism flows represent collective experiences of a similar kind, which are simultaneously or continuously realized by several related or unrelated visitors (Beritelli, Reinhold and Laesser, 2020). Understanding the spatial distribution of tourism flows and movement patterns of visitors can provide practical implications for tourism professionals regarding resource allocation, infrastructure construction, and effective tourism planning for a destination (Zhong, Sun and Law, 2019;Zhong et al, 2020), therefore tourism flows are an increasingly important topic in academia and in practice (Zhang et al, 2022).…”
Section: Theoretical Framework Of Developing a 3rd Generation Destina...mentioning
confidence: 99%
See 1 more Smart Citation
“…Tourism flows represent collective experiences of a similar kind, which are simultaneously or continuously realized by several related or unrelated visitors (Beritelli, Reinhold and Laesser, 2020). Understanding the spatial distribution of tourism flows and movement patterns of visitors can provide practical implications for tourism professionals regarding resource allocation, infrastructure construction, and effective tourism planning for a destination (Zhong, Sun and Law, 2019;Zhong et al, 2020), therefore tourism flows are an increasingly important topic in academia and in practice (Zhang et al, 2022).…”
Section: Theoretical Framework Of Developing a 3rd Generation Destina...mentioning
confidence: 99%
“…The competitiveness of the Zemplín destination should be strengthened through destination management focused on the creation of authentic and sustainable products and internal marketing with the support of public and private sector institutions (Table 3). According to the work of Beritelli et al (2015), Steiner (2015), Shoval and Ahas (2017), Baggio and Scaglione (2018), Kang et al (2018), Beritelli, Reinhold and Laesser (2020), Zhong, Sun and Law (2019), Zhong et al, (2020), Paulino, Lozano and Prats (2021) and Zhang et al (2022), we consider destinations created on the basis of administrative boundaries to be inefficient and the creation of destinations based on tourism flows as the future of destination management. Through a questionnaire survey among visitors and stakeholders, we demonstrated that the studied region is perceived as one whole, which means that there is no need for the existence of two destinations and two different DMOs, so we agree with the statements of the selected authors.…”
Section: Figure 12: Opinions On the Destination Management Organizati...mentioning
confidence: 99%
“…Different psychological mechanisms also influence consumers’ behavior through social networks ( Wang et al, 2020a , b ). Tourists increase the supply of narratives by sharing travel photos and stories ( Li and Katsumata, 2020 ; Liu et al, 2021 ; Zhang et al, 2022 ), and affective empathy has a significant mediating effect on the relationship between travel attribution and tourist intentions to online celebrity scenic spots ( Yi et al, 2021a ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, previous studies involving destination image have mainly focused on heritage and cultural tourism destinations ( Su et al, 2020a , b ); this study takes tea estates as the research object to enrich tourism destination image research. Second, psychological perception plays an important role in tourism experience ( Zhang et al, 2022 ). However, there is very limited research involving the psychological perception dimension of tourists in studies on tea estates and agricultural estates.…”
Section: Introductionmentioning
confidence: 99%